2022
DOI: 10.3389/fsurg.2022.842309
|View full text |Cite
|
Sign up to set email alerts
|

Application of Operating Room Nursing Intervention to Incision Infection of Patients Undergoing Gastrointestinal Surgery Can Reduce Complications and Improve Gastrointestinal Function

Abstract: ObjectiveTo observe the influence of nursing intervention in operation rooms on incision infection of patients undergoing gastrointestinal surgery and the improvement of gastrointestinal function.MethodsA total of 340 patients who underwent gastrointestinal surgery in our hospital from June 2020 to August 2021 were included. According to the random number table, they were divided into the conventional nursing group (n = 170) and the operating room nursing group (n = 170). The conventional nursing group was tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…All these have laid a reliable foundation for implementing CNP in TACE for HCC. CNP intervention is a kind of patient-centered targeted nursing service, which has achieved remarkable results in diseases such as children's kidney disease and hip replacement, which can effectively improve their recovery [ 21 , 22 ]. However, the application effect of interventional therapy for HCC is rarely reported.…”
Section: Discussionmentioning
confidence: 99%
“…All these have laid a reliable foundation for implementing CNP in TACE for HCC. CNP intervention is a kind of patient-centered targeted nursing service, which has achieved remarkable results in diseases such as children's kidney disease and hip replacement, which can effectively improve their recovery [ 21 , 22 ]. However, the application effect of interventional therapy for HCC is rarely reported.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative wound infections are not resolved by the application of antimicrobials or antibiotic analogues alone, but require the initiation of ongoing, systematic nursing care. Nursing intervention in the operating room requires nurses to communicate with patients and their families in a timely and effective manner during the nursing period to resolve their anxiety about surgery and improve the patients' cooperation in the perioperative period; during the surgical process, strictly control the environment of the operating room, surgical items and surgical personnel, strictly implement the aseptic operation of each link, and the surgeon, anaesthesiologists, visiting nurses, and instrument nurses cooperate with each other and closely monitor the patients' vital signs; send the patient back to the ward with the anaesthesiologist after the operation, and hand over to the ward nurses in time, stressing the postoperative precautions and observing the wound condition during the return visit, so as to reduce the rate of infection of the surgical incision and improve the satisfaction of nursing care 10,20 …”
Section: Discussionmentioning
confidence: 99%
“…At the same time, in the operating room nursing care nursing staff can also clear division of labour, do a good job in the operation of the preparation of various matters and hidden trouble detection work, the development of the surgical process is more promotional, conducive to enhance the effect of the operation, the value of nursing is very high. It has been found that the implementation of effective operating room nursing interventions in clinical practice has a positive effect on improving the prognosis of patients 10 . The impact of operating room nursing care on ovarian cyst surgery has been reported in the literature, but there is no uniform conclusion on the impact of surgical wound infection.…”
Section: Introductionmentioning
confidence: 99%
“…Standardized postoperative care and follow-up can improve the quality of life of patients. [35,36] In addition, personality, [37] and surgical wound recovery effect [38] can also have an impact on the quality of life of patients. Postoperative complications are also important contributing factors.…”
Section: Discussionmentioning
confidence: 99%